CO2 and surface temperature reduction on building surface using green walls - Aziz, Farha (2010)
Global warming due to the increase of greenhouse gaseous (GHG) emissions is an issue that plagues worldwide. It causes higher atmospheric temperatures, intensive precipitation, excessive solar radiation and increases air pollution. Consequently, it leads to the increment of energy consumption of ventilation and air conditioner in buildings in order to maintain the desirable temperature. The use of green walls has been selected as the eco-friendly approach to reduce the temperature in buildings as well as to reduce the CO2 from the ambient environment. In Malaysia, the successfulness of the green wall technology has not been thoroughly studied by the Malaysian researchers, particularly on the thermal reduction and GHG reduction. Therefore, the study evaluates the effectiveness of the green walls for outdoor ambient environment improvement and surface temperature reduction on building walls in the urban setting. Focusing on ambient air quality, this study quantify amount of carbon dioxide, carbon monoxide, surface and ambient temperature and relative humidity influenced by the green walls based on field data. Result shows that with the green wall technology, surface temperature of buildings is reduced and the ambient environment can be improved. The study also concluded that greenery can be extend to the facade of buildings to enhance air quality and thermal comfort.